ANALISIS PENGARUH KECUKUPAN MODAL, LIKUIDITAS, PROFITABILTASDAN RISIKO KREDIT TERHADAP PENYALURAN KPR PADA BANKPERSERO DAN BUSN - IKHLASUL AMAL, OKY (Jurnal Akuntansi AKUNESA, 2015)
This study aims to determine the effect of capital adequacy, liquidity, profitability, and thecredit risk of the mortgage portfolio at Bank Limited and BUSN. This analysis will be usedas a reference both for owners, investors, customers, and other stakeholders. Of the twotypes of bank, namely Bank Limited and BUSN, there are 38 companies sampled and theywill be analyzed from 2011 to 2013. The source of data that will be used in this researchare the company's annual report samples, the official website and the website of BankIndonesia and Indonesian Banking Statistics. This type of research uses quantitativeapproach with multiple linear regression method. The results showed that liquidity is theonly variable which affects the mortgage portofolio.Keywords: mortgage, capital adequacy. Liquidity, profitability, and credit risk